Keanekaragaman dan Kelimpahan Tumbuhan Air di Subak Pulagan, Tampaksiring, Gianyar, Bali - Ni Putu Bella Yuliana Dewi; I Wayan Arthana; Ni Putu Putri Wijayanti (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2018)
This study aimed to determine the diversity, abundance and dominance of aquatic plants, relation to water quality to aquatic plants, and the relation of aquatic biota to aquatic plants. This research used observation and purposive method. The highest abundance value of aquatic plants found in station 1 (upper area) of 4034 ind/m2 with the type of aquatic plant was (Salvinia molesta). The index value of diversity ranged from 0,6628-0,8985, with the highest index found in station 2 (middle) of 0,8985. The dominance index value ranged from 0,4537-0,6127, with the highest dominant index found in station 3 (lower area) with species dominated by (Pistia stratiotes). The relation of aquatic plants with temperature showed correlation value of r = -0,9967 (very strong). The relation with other water quality parameter to aquatic plants showed correlation value which were with pH of r = 0,8263 (very strong), with DO of r = -0,7651 (strong), with nitrate of r = -0,8457 (very strong), and with phosphate of r = 0,7092 (strong). Correlation between abundance of biota Aplocheilus panchax to diversity, abundance, and dominance of aquatic plants showed the highest correlation value respectively of r = 0,6344 (station 1), r = 0,9987 (station 1), and r = -0,5688 (station 3).